Dynamic Characteristics of Offshore Natural Gas Hydrate Dissociation by Depressurization in Marine Sediments - Xinfu Liu; Chunhua Liu; Jianjun Wu (Geofluids)
Dynamic characteristics of offshore natural gas hydrate (NGH) dissociation will provide the theoretical basis to analyze technical issues of oceanic hydrate exploitation. A mathematical model is developed to simulate offshore NGH dissociation by depressurization in marine sediments. Different phase combination statuses are involved in the process of NGH dissociation by taking ice melting and water freezing into account. The proposed methodology can analyze the processes of hydrate and water phase transitions, decomposition kinetics and thermodynamics, viscosity and permeability, ice-water phase equilibrium, and natural gas and water production. A set of an experimental system is built and consists of one 3-D visual reactor vessel, one isothermal seawater vessel, one natural gas and water separator, and one data acquisition unit. The experiments on offshore NGH dissociation by depressurization in 3-D marine sediments are carried out, and this methodology is validated against the full-scale experimental data measured. The results show that during the prophase, natural gas flow is preceded by water flow into the production wellbore and natural gas occupies more continuous flow channels than water under a large pressure gradient. Then, the natural gas flow rate begins to decline accompanied by an increase of water production. During the second phase, natural gas flow rate decreases slowly because of the decreased temperature of hydrate-bearing formation and low pressure gradient. The lower the intrinsic permeability in marine sediments, the later the water flow rate reaches the peak production. And the space interval of the production wellbore should be enlarged by an increase of the intrinsic permeability. The stable period of natural gas production enhances, and the water flow rate reduces with the increase of bottom-hole pressure in production wellbores. The main reason is the slow offshore NGH dissociation under the low producing pressure and the restriction of heat conductivity under the low temperature.